Beginning Object-Oriented ASP.NET 2.0 with VB .NET From Novice to Professional - Myers, Brian. (Apress : Imprint: Apress, 2005)
Beginning Object-Oriented ASP.NET 2.0 with VB .NET covers all of the basics, from definition to inheritance. This book even includes a chapter on Visual Studio 2005 and Microsoft .NET Framework 2.0, enabling you to create ASP.NET 2.0 applications. Also included are chapters on creating web forms, web controls, and web services. Code samples illustrate the usage of each concept.